Management of pediatric ankle fractures: comparison of biodegradable PLGA implants with traditional metal screws - Nudelman, Hermann; Lőrincz, Aba; Lamberti, Anna Gabriella; Varga, Marcell; Kassai, Tamás; Józsa, Gergő (Frontiers in Pediatrics, 2024)
Biodegradable implants are growing in popularity. As their relevance in modern clinical practice has gained importance, we wanted to evaluate their use in pediatric fractures. This study aims to evaluate the effects and outcomes of ankle fracture treatment with absorbable implants compared to metal screws. In a retrospective review, a total of 128 patients were under observation, with distal tibial fracture types ranging from Salter-Harris II-IV. In group A, patients were treated with poly L-lactide-co-glycolic acid (PLGA) absorbable screws (n=76). Group B included patients treated with metal screws (n=52). The extremities were placed in a cast for six weeks after surgery and were utilized for another 6-8 weeks. Patients were followed up for 12-30 months and were evaluated accordingly. The authors examined several aspects such as age, gender, open or closed repair, mechanism of injury, length of hospitalization, type of fracture, time of recovery, and complications. There were no statistically significant differences between the groups regarding demographic qualities, such as age, type of fracture, side of injury, and length of cast application (Table 1, p > 0.05 in all cases). Therefore, the groups were assumed to be homogeneous. Out of 76 patients in group A, only two presented with complications, so reoperation took place. The rest healed without complications or refractures. Two of those treated with metal screws (n=52) had minor, and four had major complications with reoperation. In pediatric cases, applying absorbable implants presents excellent results for treating ankle fractures. It does not disturb the growth plate and does not require reoperation. For this reason, it reduces the burden on the patient and the healthcare provider while simultaneously decreasing the risk of complications, such as infections or problems due to general anesthesia.This retrospective multi-centre cohort study was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. The patients examined in this study were presented to the two Hungarian pediatric trauma centers at the